2014
DOI: 10.1186/1556-276x-9-309
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental role of arsenic flux in nanohole formation by Ga droplet etching on GaAs(001)

Abstract: Nanoholes with a depth in the range of tens of nanometers can be formed on GaAs(001) surfaces at a temperature of 500°C by local etching after Ga droplet formation. In this work, we demonstrate that the local etching or nanodrilling process starts when the Ga droplets are exposed to arsenic. The essential role of arsenic in nanohole formation is demonstrated sequentially, from the initial Ga droplets to the final stage consisting of nanoholes surrounded by ringlike structures at the surface and Ga droplets con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 36 publications
4
21
0
Order By: Relevance
“…Small holes are visible only on the AlGaAs surface that we attribute to defects caused by contamination of the highly reactive AlGaAs surface during the 1-h growth interruption. These results are in agreement with a very recent study of Fuster et al [ 44 ], which shows that droplet etching with Ga at T =500°C is only possible in the presence of an arsenic flux. Additional experiments [ 42 ] show that hole formation is also suppressed for F As >3×10 −6 Torr and that flat surfaces are formed, instead.…”
Section: Resultssupporting
confidence: 93%
“…Small holes are visible only on the AlGaAs surface that we attribute to defects caused by contamination of the highly reactive AlGaAs surface during the 1-h growth interruption. These results are in agreement with a very recent study of Fuster et al [ 44 ], which shows that droplet etching with Ga at T =500°C is only possible in the presence of an arsenic flux. Additional experiments [ 42 ] show that hole formation is also suppressed for F As >3×10 −6 Torr and that flat surfaces are formed, instead.…”
Section: Resultssupporting
confidence: 93%
“…A second important process is the removal of the liquid material from the initial droplet position. Previous studies indicated already that a small amount of background arsenic is essential for this [ 17 , 18 ]. Without background As, the initial droplets are conserved and no holes are formed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a variety of quantum structures have been obtained by this technique such as dots, rings, holes, wires, dot pairs, dot disks, which can be fabricated on any sort of substrates. This flexible nanostructure-fabrication technique can apply to a wide range of materials by precisely controlling the lateral diffusion of metallic droplets and crystallization process [ 11 , 12 ]. Besides, many applications have been proposed by droplet epitaxy technique: GaAs/AlGaAs quantum dot laser [ 13 ], single photon emitter on Si [ 14 ], and infrared photodetector with strain-free GaAs quantum dot pairs [ 15 ].…”
Section: Introductionmentioning
confidence: 99%